Groin Hernias in Women—A Review of the Literature - Köckerling, Ferdinand; Koch, Andreas; Lorenz, Ralph (Frontiers in Surgery, 2019)
Background: To date, there are few studies and no systematic reviews focusing specifically on groin hernia in women. Most of the existing knowledge comes from registry data. Objective: This present review now reports on such findings as are available on groin hernia in women. Materials and Methods: A systematic search of the available literature was performed in September 2018 using Medline, PubMed, Google Scholar, and the Cochrane Library. For the present analysis 80 publications were identified. Results: The lifetime risk of developing a groin hernia in women is 3–5.8%. The proportion of women in the overall collective of operated groin hernias is 8.0–11.5%. In women, the proportion of femoral hernias is 16.7–37%. Risk factors for development of a groin hernia in women of high age and with a positive family history. A groin hernia during pregnancy should not be operated on. The rate of emergency procedures in women, at 14.5–17.0%, is 3 to 4-fold higher than in men and at 40.6% is even higher for femoral hernia. Therefore, watchful waiting is not indicated in women. During surgical repair of groin hernia in females the presence of a femoral hernia should always be excluded and if detected should be repaired using a laparo-endoscopic or open preperitoneal mesh technique. A higher rate of chronic postoperative inguinal pain must be expected in females. Conclusion: Special characteristics must be taken into account for repair of groin hernia in women.